PERAN DIGITAL SKILLS SUMBER DAYA MANUSIA DALAM PERCEPATAN PROSES KLAIM BERBASIS RESOURCE-BASED THEORY (RBT) DAN VRIO PADA PERUSAHAAN PIALANG ASURANSI DI INDONESIA - Dewi Haryuni Noor Roslim; Awang Darmawan Putra (Management and Leadership Study Programme, 2026)
Digital transformation in the insurance industry requires organizations not only to adopt technology but also to ensure that their human resources are ready to utilize it optimally. However, in practice, the claims process still often experiences delays, impacting service quality and customer satisfaction. This study aims to analyze the role of human resource digital skills in accelerating the claims process at insurance Broker companies in Indonesia, employing a qualitative approach through the Systematic Literature Review (SLR) method. The data were collected from scientific articles and institutional publications obtained through Google Scholar and credible websites between 2022 and 2026. From the initial 50 identified articles, a rigorous selection process was conducted based on relevance and methodological quality to examine the role of digital skills in improving operational efficiency, communication quality, and the accuracy of information management in the claims process. The findings indicate that digital skills play an important role in enhancing work process efficiency, strengthening digital communication, improving the accuracy of information management, and accelerating coordination among parties involved in the claims process. Based on the perspective of Resource-Based Theory (RBT) and the VRIO framework, digital skills can be categorized as strategic resources that are valuable, relatively rare, difficult to imitate (inimitable), and require organizational support (organized), thereby creating sustainable competitive advantage. This research provides theoretical contributions by integrating the concepts of digital skills and RBT within the context of insurance Broker companies, as well as practical implications for the development of digital-based human resource strategies.